Effect of argon implantation on solid-state dewetting: control of size and surface density of silicon nanocrystals. (20th December 2016) - Almadori, Y; Borowik, Ł; Chevalier, N; Barbé, J-C
Abstract: Thermally induced solid-state dewetting of ultra-thin films on insulators is a process of prime interest, since it is capable of easily forming nanocrystals. If no particular treatment is performed to the film prior to the solid-state dewetting, it is already known that the size, the shape and the density of nanocrystals is governed by the initial film thickness. In this paper, we report a novel approach to control the size and the surface density of silicon nanocrystals based on an argon-implantation preliminary surface treatment. Using 7.5 nm thin layers of silicon, we show that increasing the implantation dose tends to form smaller silicon nanocrystals with diameter and height lower than 50 nm and 30 nm, respectively. Concomitantly, the surface density is increased by a factor greater than 20, going from 5 μ m −2 to values over 100 μ m −2 .